Management of asthma during pregnancy - Diego J. Maselli (Therapeutic Advances in Respiratory Disease, 2013)
Asthma is an inflammatory lung condition that is the most common chronic disease affecting pregnancy. The changes in pulmonary physiology during pregnancy include increased minute ventilation, decreased functional residual capacity, increased mucus production, and airway mucosa hyperemia and edema. Pregnancy is also associated with a physiological suppression of the immune system. Many studies have described the heterogeneous immune system response in women with asthma during pregnancy, which partly explains why asthma has been shown to worsen, improve, or remain stable in equal proportions of women during pregnancy. Asthma may be associated with poor maternal and fetal outcomes. However, better maternal and fetal outcomes are observed with better asthma control. Asthma controller medications are generally thought to be safe during pregnancy, but limited data are available for some of the medicines. Newer medications like omalizumab open avenues for the treatment of asthma, but also pose a challenge, as there is limited experience with their use. Therefore, a multidisciplinary approach, including obstetricians, asthma specialists, and pediatricians should collaborate with the patient to carefully weigh the risks and benefits to determine an optimal management plan for each individual patient. The aim of this review article is to summarize the most recent literature about the immunological changes that occur during pregnancy, physiological and clinical implications of asthma on pregnancy, and asthma management and medication use in pregnant women.